2020
DOI: 10.1001/jamadermatol.2020.0001
|View full text |Cite
|
Sign up to set email alerts
|

Association of Indoor Tanning Regulations With Health and Economic Outcomes in North America and Europe

Abstract: he incidence of skin cancer in fair-skinned populations is high and increasing globally [1][2][3] such that total health care spending on its treatment is among the highest of all cancers in countries such as the United States, Denmark, and Australia. [4][5][6] The most common skin cancers are basal cell carcinomas (BCCs) and squamous cell carcinomas (SCCs) (collectively known as keratinocyte carcinomas). Melanoma is less common overall but is the most frequently diagnosed cancer in young adults 7 and is more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 77 publications
1
16
0
Order By: Relevance
“…Indoor tanning rates among US high school students declined from 15.6% in 2009 to 7.3% in 2015, although white, non-Hispanic young women continue to have the highest rates of usage [ 25 ]. A JAMA Dermatology economic analysis from 2020 concluded that banning indoor tanning among those under 35 could avert 448,000 cases of melanomas [ 26 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Indoor tanning rates among US high school students declined from 15.6% in 2009 to 7.3% in 2015, although white, non-Hispanic young women continue to have the highest rates of usage [ 25 ]. A JAMA Dermatology economic analysis from 2020 concluded that banning indoor tanning among those under 35 could avert 448,000 cases of melanomas [ 26 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…The increase in indoor tanning restrictions may explain reductions in the number of indoor tanning providers, consumer spending on indoor tanning [5], and past-year indoor tanning among girls (24.1% in 2009 and 9.5% in 2015) and boys (5.7% in 2009 and 3.3% in 2015) attending high school and young adults aged 18-34 years (14% in 2007 and 4% in 2018) in the United States in recent years [3,6]. More stringent regulations have been associated with greater reductions in indoor tanning behavior and have been estimated to have a greater impact on melanoma incidence, mortality, and cost [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In a large study in France, parents with a lower understanding of sun safety measures and less stringent protection behaviours had children engaging in fewer sun protection practices than children of parents who did practise sun protection [ 24 ]. Legislation banning commercial sunbeds sends a clear message from the government that they are protecting citizens’ health, and moreover it is highly likely to be an investment that will save healthcare costs in the longer-term [ 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Published point estimates for 15- to 19-year-old use in England from before the 2010 ban on sunbeds for under 18-year-olds [ 2 ] were projected to 2020 based on this two-yearly proportional decrease. Comparing the English projected estimate with <20-year-old European prevalence for 2020, extrapolated using the same trend from the 2012 and 2014 estimates, indicated that the ban further reduced sunbed use in adolescents by 39 percentage points [ 14 , 16 ].…”
Section: Methodsmentioning
confidence: 99%